Excess hydrogen sulfide and polysulfides production underlies a schizophrenia pathophysiology. Issue 12 (28th October 2019) - Ide, Masayuki; Ohnishi, Tetsuo; Toyoshima, Manabu; Balan, Shabeesh; Maekawa, Motoko; Shimamoto‐Mitsuyama, Chie; Iwayama, Yoshimi; Ohba, Hisako; Watanabe, Akiko; Ishii, Takashi; Shibuya, Norihiro; Kimura, Yuka; et al.
Abstract: Mice with the C3H background show greater behavioral propensity for schizophrenia, including lower prepulse inhibition (PPI), than C57BL/6 (B6) mice. To characterize as‐yet‐unknown pathophysiologies of schizophrenia, we undertook proteomics analysis of the brain in these strains, and detected elevated levels of Mpst, a hydrogen sulfide (H2 S)/polysulfide‐producing enzyme, and greater sulfide deposition in C3H than B6 mice. Mpst ‐deficient mice exhibited improved PPI with reduced storage sulfide levels, while Mpst ‐transgenic (Tg) mice showed deteriorated PPI, suggesting that "sulfide stress" may be linked to PPI impairment. Analysis of human samples demonstrated that the H2 S/polysulfides production system is upregulated in schizophrenia. Mechanistically, the Mpst‐ Tg brain revealed dampened energy metabolism, while maternal immune activation model mice showed upregulation of genes for H2 S/polysulfides production along with typical antioxidative genes, partly via epigenetic modifications. These results suggest that inflammatory/oxidative insults in early brain development result in upregulated H2 S/polysulfides production as an antioxidative response, which in turn cause deficits in bioenergetic processes. Collectively, this study presents a novel aspect of the neurodevelopmental theory for schizophrenia, unraveling a role of excess H2 S/polysulfides production. Synopsis: This study proposes a novel concept that excess hydrogen sulfide production (sulfide stress) underlies a schizophrenia pathophysiology in the realm of neurodevelopmental hypothesis of the disease. Targeting the metabolic pathway of hydrogen sulfide provides a novel therapeutic approach. Mpst‐deficient mice exhibited improved prepulse inhibition (PPI), a typical schizophrenia‐relevant endophenotype, with reduced sulfide levels, while Mpst‐transgenic mice showed deteriorated PPI. Postmortem brains and iPS‐derived cells from a subset of schizophrenia patients displayed evidence for sulfide stress. Sulfide stress condition stemmed from insults in developing brain in mouse models and elicited dampened energy metabolism. MPST expression level in hair follicles has a potential to stratify schizophrenia patients with sulfide stress. Abstract : This study proposes a novel concept that excess hydrogen sulfide production (sulfide stress) underlies a schizophrenia pathophysiology in the realm of neurodevelopmental hypothesis of the disease. Targeting the metabolic pathway of hydrogen sulfide provides a novel therapeutic approach.